The Role of Internal Auditors in Preventing Fraud in Government - Sarah Vika Sabrina; Adek Wahyuni Safitri; Dwi Salsabila Ilham; Khairani Yahya; Galih Supraja (CV. AFDIFAL MAJU BERKAH, 2025)
Government institutions play an important role in the achievement of a country to achieve a goal is supported by a good attitude and action from a state civil apparatus. Sometimes bad things and actions are carried out to realize all of their ambitions. Based on The Association of Certified Fraud Examiners (ACFE), fraud is an act carried out to achieve a goal, such as manipulating financial statements or providing false information. Broadly speaking, forms of fraud often occur in government institutions (corruption). In Tuanakotta (2007) explained that the fraud triangle is a model to explain a number of factors that cause a person to carry out fraudulent work, which is corruption. The approach of this research is a type of research (case study). According to Ningsih (2019): Qualitative research is research that intends to deeply understand the processes, challenges, and strategies used by internal auditors in preventing fraudSome of the main results of relevant study studies usually include: Effectiveness of internal supervision Internal auditors are tasked with ensuring that the internal control system is running properly to detect and prevent potential fraud. 1. Increased anti-fraud awareness The existence of internal auditors encourages government employees' awareness of the importance of ethics, accountability, and transparency. 2. Early detection of potential fraud Through periodic audits and special investigations, internal auditors are able to identify suspicious activity before it becomes a larger fraud. 3. Strengthening organizational culture Internal auditors are often involved in building an organizational culture that focuses on honesty and compliance with rules.